Contemporary and Gramscian Critical Socio-Historical Views on State and Revolutions - Di Bonaventura, Florence (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
This paper intends to feed a methodological, theoretical and philosophical reflexion on the critical perspectives historical and political sociology can imply or afford as regards the formation of the modern State and its developments. Indeed, whether they are classical or contemporary, many political sociologists or socio-historians have bequeathed or proposed socio-historical intuitions, (self-) critical reflexions or innovative tools enabling us to better understand the relations between the State and (civil) society as well as the power relations that could lead to stability or instability of political regimes over time; and to enrich contemporary debates on the meanings of the State, democracy and related concepts. These authors of the past and the present have often been questioning and critical, enabling us to relativise the Eurocentric and deterministic character historical sociology is sometimes "accused" of, whereof its authors were or are more or less conscious.